Preliminary Survey of Water Hyacinth in Lake - Dereje Tewabe (Global Journal of Allergy - Peertechz Publications, 2015)
Investigation of water hyacinth was conducted from October 27, 2011 to November 3, 2011 by interdisciplinary expedition groups. A total of 24 sites were delineated using geographical positioning system (GPS) during investigation of water hyacinth incidence along the whole periphery of Lake Tana. Water hyacinth was started from Mitreha Abawarka kebele of Gondar zuria woreda specifically around at Netseba village with an estimated of 3 hectare area coverage. Highest infestation of the weed was observed at Megech River mouth with estimated area coverage of c. 80-100 hectare. Its infestation extends up to Dirma River mouth. Especial adaptation of water hyacinth on land based conditions at which soil moisture relatively high was observed around Tana woina kebele of Gondar zuria woreda adjacent lake shore side. The incidence and depth of water hyacinth infestation in Lake Tana is still at its infant stage, because except the North and to some extent North-east direction, the other parts of Lake Tana were devoid of the water hyacinth. Generally water hyacinth remains a major problem in Lake Tana where effective control programs are not in place as soon as possible.